Valuation of IPO Companies in the IT industry in China with Financial and Non-Financial Information - CAI, Jing (2017)
This study investigates the valuations of initial public offering (IPO) firms in IT the industry in China from two perspectives: Firstly, this study examines the correlations between the valuation of IPO firms in IT the industry in China and a set of financial and non-financial information. The financial information is selected according to previous researches research that demonstrate the financial information is value-relevant and the non-financial information is selected on the basis of data accessibility and characteristics of the Chinese IT industry. Secondly, two valuation methods: the direct valuation method and the relative valuation method are adopted in this paper. After analyzing the direct valuation and the relative valuation, the comparison results between the two methods in finding value drivers for valuation of IPOs in Chinese IT industry are presented.